Pengaruh penambahan Lactobacillus plantarum dalam pembuatan mie kering berbahan rambut jagung manis (Zea mays var. Saccharata) - Pradhanawati, Lintang; Darmayasa, Ida Bagus Gede; Parwanayoni, Ni Made Susun (Jurnal Biologi Udayana; Vol 28 No 1 (2024): JURNAL BIOLOGI UDAYANA, 2024)
Rambut jagung manis is one of the agricultural waste products that is still minimally processed. One form of processed rambut jagung manis as a basic ingredient for making dry noodles. However, the resulting noodle product has a weakness in the form of a short shelf life due to the presence of spoilage fungi such as mold. Therefore, efforts need to be made to reduce the amount of mold by adding Lactic Acid Bacteria ( L. plantarum ). The method used in this research was an experimental method with a completely randomized factorial design (RALF), namely factor I L. plantarum concentration (0%, 2%, 4%, 6% (v/v)) and factor II storage time (0 days, 5 days, and 10 days) with 3 repetitions, so that 36 experimental units were obtained. The parameters measured in this study were the degree of acidity (pH), mold numbers, and nutritional value. The results showed that the average mold number at T0 was 3.40 ± 0.109 in dry noodles made from corn silk which were fermented without adding L. plantarum. Meanwhile at concentrations of 2%, 4% and 6% respectively as follows 3.24 ± 0.174; 3.30±0.240; and 3.34 ± 0.000. Mold content (Aspergillus sp.). Nutrient content tests after storage on the 10th day (T2) in L . plantarum concentration treatments of 0%, 2%, 4%, and 6% showed protein levels of 16.05%; 18.13%; 20.04%; and 20.36% bw and glucose levels respectively 78.87%; 83.16%; 81.56%; and 78.84%. The numerical value of yeast mold population in mie from rambut jagung during storage can be reduced and the protein content increases so that the addition of L. plantarum can be used as food biopreservative.